The Use of Membrane Lipid Replacement with Glycerophospholipids to Gradually Decrease the Self-Reported Symptom Severities in Chemically Exposed Gulf War Veterans - Nicolson, Garth L.; Breeding, Paul C. (Medical Science: Trends and Innovations Vol. 13, 2025)
Approximately 700,000 United States armed forces personnel, along with armed forces from 30 coalition countries, were deployed to the Persian Gulf in 1991-1992 for support of military operations (Operation Desert Shield/Operation Desert Storm) that are now known as the 1991 Gulf War. A large fraction of veterans of the 1991 Gulf War slowly developed multi-symptom chronic illnesses that have been termed Gulf War Illnesses (GWI). Many, if not the majority, of these GWI patients were chemically exposed, and they now have few alternatives for the treatment of their symptoms. Membrane Lipid Replacement (MLR) with oral membrane glycerophospholipids has been used as a safe and effective approach for slowly extracting and removing hydrophobic organic molecules from cells and tissues by the process of chemical partitioning into phospholipid structures and exchange by a mass action process. In addition, MLR also enhances mitochondrial function. This combination treatment can decrease the severity of certain signs and symptoms associated with a variety of multi-symptom illnesses, including those environmental illnesses associated with chemical contamination. A preliminary open-label study was conducted on 20 male veterans who were deployed to combat areas in Kuwait and Iraq during the 1991 Gulf War and were exposed to toxic chemicals. These veterans subsequently became ill with GWI and were utilised in this pilot study. This clinical study was designed as an open-label, Institutional Review Board-approved, preliminary or pilot clinical trial to study the effects of an all-natural glycerophospholipid chewable wafer supplement (Patented Energy® with NTFactor® Lipids) on the severity of signs and symptoms of GWI patients over a 6-month period. The subjects took 6 g per day of the all-natural, oral MLR glycerophospholipids, and the severities of over 100 signs and symptoms were self-reported at various times using illness survey forms. Sixteen subjects in the study were fully compliant and completed the study. There were gradual and significant reductions of symptom severities in these patients in categories related to fatigue, pain, musculoskeletal, nasopharyngeal, breathing, vision, sleep, balance, urinary, gastrointestinal symptoms and chemical sensitivities. During the Gulf War, veterans were variously exposed to a number of chemical, biological, and radiological sources, in addition to physical and mental stressors. In addition, GWI patients were exposed to combinations of multiple agents and stressors, and this makes any treatment approach much more complex. During the study, there were no adverse incidents, and the study supplement was extremely well tolerated. It is concluded that MLR with moderate amounts of oral glycerophospholipids appears to be a safe, simple and potentially effective method for slowly reducing the severity of multiple symptoms in chemically exposed veterans with multi-symptom illnesses (GWI). In addition, MLR also enhances mitochondrial function. This treatment was successfully used to slowly decrease the severity of certain signs and symptoms of chemically exposed veterans of the 1991 Gulf War.